The need to understand innovative activity as a capital-forming process in the accounting system - V.K. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The compliance of the current accounting system with the needs of interested parties regarding the innovative activity of the enterprise has been analyzed. Dissatisfaction of interested users with information about research and development, formed in the accounting system, has been considered. The requirements of international and national accounting standards (IAS/IFRS, GAAP US, S(S)A) regarding the capitalization of research and development costs have been analyzed. The use of a cost-forming approach to understanding innovative activity in the accounting system has been considered. The inconsistency of the accounting and economic approaches to understanding the innovative activity of the enterprise has been established. The need to use a capital-forming approach to understanding the essence of innovative activity in the accounting system to meet the growing needs of users in the conditions of the knowledge economy has been substantiated. The need to use the integrated concept of «innovation capital» in accounting for the development of a new system of accounting and reporting on innovative initiatives, prospects and risks to the innovative policy and strategy of the enterprise has been proposed.